Phospholipid oxidation generates potent anti‐inflammatory lipid mediators that mimic structurally related pro‐resolving eicosanoids by activating Nrf2. Issue 5 (13th March 2015) - Bretscher, Peter; Egger, Julian; Shamshiev, Abdijapar; Trötzmüller, Martin; Köfeler, Harald; Carreira, Erick M; Kopf, Manfred; Freigang, Stefan
<x xml:space="preserve">Abstract</x> This study characterizes the potent anti‐inflammatory bioactivity of oxidized phospholipids and identifies a fatty acid epoxycyclopentenone as the active component that triggers Nrf2 signaling in myeloid cells and alleviates inflammation and endotoxin‐induced lung injury in a mouse model.